Low prevalence of mismatch repair deficiency in Chinese colorectal cancers: a multicenter study. (10th April 2020) - Jiang, Wu; Sui, Qiao-Qi; Li, Wen-Liang; Ke, Chuan-Feng; Ling, Yi-Hong; Liao, Le-En; Zhu, Zhu; Cai, Mu-Yan; Luo, Jun; Mao, Lin-Lin; Zhang, Hui-Zhong; Wan, De-Sen; et al.
Abstract: Background: Although universal testing for mismatch repair deficiency (dMMR) has been recommended to all colorectal cancer (CRC) patients, related evidence for the Chinese population is lacking. Here, we investigated the prevalence and clinicopathological features of dMMR patients in a large Chinese CRC cohort. Methods: We included 7, 373 CRC patients treated at four Chinese medical centers between August 2010 and September 2016. Patients' baseline characteristics and pathological features were recorded. The clinicopathological features were compared between patients with MLH1/PMS2 deficiency (dMLH1/PMS2) and MSH2/MSH6 deficiency (dMSH2/MSH6). Results: Among the investigated patients, 654 (8.9%) were identified with dMMR CRCs and, of them, 401 (61.3%) were males, with a median age of 55 years (range, 22–87 years); 355 (54.3%) had stage II CRC based on American Joint Committee on Cancer 8th edition. The prevalence of the dMLH1/PMS2 group and the dMSH2/MSH6 group were 51.5% (337/654) and 25.1% (164/654), respectively. Compared with dMSH2/MSH6 patients, those with dMLH1/PMS2 were older (57 vs 52 years, P  <   0.001), more likely to be female (45.7% vs 31.5%, P  =   0.004), prone to having tumors located in the right-hand side of the colon (59.0% vs 47.6%, P  =   0.015), and less likely to have a family history of tumors (29.7% vs 43.3%, P  =   0.003). Conclusions: The prevalence of dMMR in Chinese CRC patients was low, especially in the dMLH1/PMS2 group. The clinicopathological features were different between dMMR subgroups.